"Ja" rekolekcjonisty w książce Adama Szustaka OP pod tytułem "Plaster miodu" = A retreat preacher's "I" in a book entitled "Honeycomb" ["Plaster miodu"] by Adam Szustak O.P. [Ordo Praedicatorum] - Jatczak, Paulina; Pietrzak, Magdalena (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The material basis of the sketch is a modified record of Advent retreats named "Honeycomb" delivered by a popular Dominican preacher Adam Szustak in 2014. The analysis was carried out in two ways.
Keywords: Szustak, Adam (1978- ); rekolekcje; świadectwo; nadawca; retreats; testimony; addresser